Respuesta :
Add the two rows together
-5x = 10
Solve for x in the above equation
x = -2
Substitute x = -2 into any of the two equations. Let's pick the firs equation; -3x - 4y = 7
-3 × -2 - 4y = 7
Solve for y in the above equation
y = -1/4
Therefore,
x = -2
y = -1/4
Answer:
x = -2
Step-by-step explanation:
So in this problem what you have to do is use the tool elimination so it would look something like this:
-3x - 4y = 7
+ -2x +4y = 3 So what you are doing here is adding these together.
----------------------
x = -2
Further explained.
Basically you are going left to right adding the like terms together. For example, -3x + -2x= -5x. And then you would continue doing this until you come to a final equations, which for this one would be -5x = 10. And then solve to get -2.
The next step would be to plug your x into one of the above equations.
Your y would be -1/4.